A Development of Homolog Sequence of Eimeria tenella Partial Genome as a Probe for Molecular Diagnosis of Coccidiosis - S. Sumartono (Universitas Gadjah Mada, 2005)
The goal of the research was to develop a homolog sequence of Eimeria tenella partial genome as a molecular probe for diagnose coccidiosis using dot blot method. A probe of homolog sequence of E.tenella partial genome and a non radioactive label, dig-11-dUTP, were used for this research. Four concentrations of molecular probe labeled with dig-11-dUTP, namely, 158,33 pg/µl, 52,25 pg/µl, 15,83 pg/µl and 5,225 pg/µl were tested to detect 0,6551 µg DNA target. The procedure of labeling and hybridization detection between DNA target with the molecular probe labeled with dig-11-dUTP were carried out with Digh high prime DNA labeling and detection starter Kit I. The conclusion of the research was that 52,25 pg/µl molecular probe or more which its sequence GGCA CAGTATCCTCCTTCAGGGCAGGG CTCGCACTGGTCAAA CGCGG TAC CATT could detect DNA target by dot blot method.